An Organizational Framework for Microenterprises to Face Exogenous Shocks: A Viable System Approach - Denny Suarez Ambriz; Jacqueline Y. Sánchez-Garcia; Juan E. Núñez-Ríos (Administrative Sciences)
This study examines how integrating the critical components of entrepreneurial orientation (EO) can improve the adaptability of microenterprises by applying the Viable System Model (VSM). Given the crucial role of microenterprises in job creation, entrepreneurship promotion, and social cohesion, the need for approaches that ensure their success in turbulent environments is highlighted. We applied Social Network Analysis (SNA) to analyze a co-occurrence network to identify critical EO factors relevant to microenterprises and to understand how authors relate them to the structure of the VSM using a Californian microenterprise as a conceptual model. These factors include innovation, autonomy, control implementation, market orientation, and change management, organized into the five functions of the VSM. The results suggest that this conceptual framework strengthens organizational responsiveness in disruptive environments, promoting internal cohesion and more informed decision-making. Although the specific characteristics of each microenterprise require adjusting the VSM to their particular needs, this study provides a solid basis for applying the key elements of EO in the VSM, underscoring the need for further research to adapt this approach to different contexts to improve organizational agility in the face of exogenous shocks.